Developing brains and changing worlds: macroenvironmental changes and their association with brain development - Quinones, Juan Felipe; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; Garavan, Hugh; Gowland, Penny; Grigis, Antoine; Heinz, Andreas; Lemaitre, Herve; Martinot, Jean-Luc; Paillère Martinot, Marie-Laure; et al. (Environmental research, 2026)
Growing evidence suggests that physical environmental features at the neighborhood level are linked to brain structure during human development. In a context of accelerated urbanization, climate change and technological transformations, assessing how environmental changes relate to brain development is critical. Most studies to date, however, used cross-sectional data only and focused on a reduced set of environmental and brain features. The present study investigates whether macroenvironmental and brain changes are associated during adolescence. We used structural equation models and regularized multivariate path analysis to identify macroenvironmental features that predict changes in whole-brain structural features in a sample of 368 individuals from the IMAGEN study (https://www.imagen-project.org/), who were assessed at 14 and 22 years of age. We observed characteristic brain developmental changes and substantial individual differences in change in 15 macroenvironmental features. Path analysis showed that changes in a handful of these variables, for instance tree cover density, presence of water bodies and air pollution, significantly predict changes in cortical thickness, structural connectivity and gray and white matter volumes over adolescence.
Online verfügbar: 2. Januar 2026, Artikelversion: 16. Januar 2026
Gesehen am 26.02.2026